LITERATURE ANALYSIS: MEASURING TOOL FOR ENVIRONMENTAL LITERACY IN PEATLAND INTEGRATION SCIENCE LEARNING - Rini Rianty; Santiani Santiani; Hadma Yuliani; Nadia Azizah (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2024)
Peatlands play a crucial role in maintaining environmental balance and mitigating global climate change. Peatland damage due to human activities continues to occur. One of the efforts to deal with this problem is to improve students' environmental literacy through science learning that integrates peatlands. This study aims to analyze the dimensions and indicators used in the development of environmental literacy measurement tools in peatland integration science learning. The method used is Systematic Literature Review (SLR). The results of the analysis show that environmental literacy measurement tools generally cover four main dimensions, namely environmental knowledge, attitudes towards the environment, cognitive skills, and environmental behavior or participation, with specific indicators in each dimension. The majority of existing measurement tools have not specifically integrated the peatland context. However, some recent studies have begun to develop environmental literacy measurement tools by integrating the peatland context. One example is the development of a questionnaire specifically designed to measure environmental literacy in peatland areas. The development of peatland-integrated environmental literacy measurement tools in science learning to increase students' understanding and concern for peatland conservation is urgently needed.